Early Application of Neuromuscular Electrical Stimulation Prevents Excessive Muscle Wasting in Critically Ill Patients in the Intensive Care Unit - Utama Hutapea, Johannes Diandra Indra; Subadi, Imam; Arfianti, Lydia; Semedi, Bambang Pujo; Melaniani, Soenarnatalina (Universitas Airlangga, 2025)
Background: Intensive Care Unit-Acquired Weakness (ICU-AW) is a common neuromuscular complication in critically ill patients, leading to muscle atrophy, prolonged mechanical ventilation and impaired functional recovery. Effective rehabilitation strategies play crucial role in maintaining muscle strength. Neuromuscular electrical stimulation (NMES) had shown potential in preserving quadriceps femoris muscle thickness. This study aimed to examine the effect of NMES to quadriceps femoris muscle thickness in patient with ICU-AW.Methods: Patients that stayed in ICU more than 48 hours and used mechanical ventilation for at least 24 hours enrolled in one-group pretest-posttest design. Neuromuscular electrical stimulation applied to bilateral quadriceps femoris for 30 minutes daily over five consecutive days. Bilateral quadriceps femoris muscle thickness were assessed with USG day before and after therapy.Results: Twenty ICU-AW patients were enrolled from December 2023 to June 2024, and 13 of them completed the study. There were no significant changes in the thickness of the right and left quadriceps femoris muscle before and after 5-days of NMES therapy (p = 0.910 and p = 0.519, respectively). However, we preserved less than 5% decreased of muscle thickness.Conclusions: Early 5-days of NMES therapy did not increase quadriceps femoris muscle thickness but effectively prevented further muscle degradation in ICU-AW patients. The potential benefits of rehabilitation therapy in ICU-AW patients should be further explored in future studies with controlled indicators and larger sample sizes.